2002
DOI: 10.1136/pmj.78.915.47
|View full text |Cite
|
Sign up to set email alerts
|

Necrotising fasciitis in a patient receiving infliximab for rheumatoid arthritis

Abstract: A case of necrotising fasciitis in a patient receiving infliximab, an antitumour necrosis factor alpha (TNF-α) agent for rheumatoid arthritis, is presented. A widespread confluent, erythematous, pustular skin rash was the presenting sign. There was no fever throughout this admission. β-Haemolytic group A streptococcus was isolated from blood cultures and skin swabs. The adductor muscles and fascia around the site of a previous hip arthroplasty were necrotic on exploration. The case highlights the risk of sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(36 citation statements)
references
References 8 publications
3
31
0
2
Order By: Relevance
“…These data suggested that TNF-a, but not IL-1R or TLR2, is involved in host defense against GAS soft tissue infection. Interestingly, these findings are in accordance with reports that anti-TNF-a therapy may increase the risk for GAS NF in rheumatoid arthritis and dermatomyositis patients (31,32).…”
Section: Resultssupporting
confidence: 82%
“…These data suggested that TNF-a, but not IL-1R or TLR2, is involved in host defense against GAS soft tissue infection. Interestingly, these findings are in accordance with reports that anti-TNF-a therapy may increase the risk for GAS NF in rheumatoid arthritis and dermatomyositis patients (31,32).…”
Section: Resultssupporting
confidence: 82%
“…We next examined the expression pattern of TNF-α, a cytokine involved in the augmentation of inflammatory responses to bacterial infection. Indeed, development of GAS-necrotizing fasciitis has been reported as a complication of anti-TNF-α therapy (37). As shown in Figure 7A, GAS strongly induced TNF-α mRNA production in WT macrophages.…”
Section: Figurementioning
confidence: 86%
“…3, 4 We report herein 5 cases of interstitial granulomatous dermatitis (IGD) occurring in patients receiving 4 different agents with TNF-␣ inhibitory activity.…”
Section: Umor Necrosis Factormentioning
confidence: 99%